Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1570-7458.2010.01008.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization effects on Myzus persicae aphid dynamics on peach: vegetative growth allocation or chemical defence?

Abstract: Plant nitrogen (N) fertilization is a common cropping practice that is expected to serve as a pest management tool. Its effects on the dynamics of the aphid Myzus persicae (Sulzer) (Hemiptera: Aphididae) were examined on young peach [Prunus persica (L.) Batsch (Rosaceae)] trees grown under five N treatments, ranging from N shortage to supra‐optimal supply for growth. Aphid population increased over time at the three intermediate N levels. It remained stable at the lowest N level and decreased at the highest N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 56 publications
0
44
0
Order By: Relevance
“…However, in a study with Mysus persicae on grafted one-year-old peach plants and five levels of nitrogen fertilisation (0.05, 3, 6, 10 and 15 mM N from NO 3 ) [59], it was found that populations which had developed from initially placed apterous aphids, remained stable at the lowest N level, increased over time at the three intermediate levels and decreased at the highest level. Another study with populations of Aphis nerii, begun from apterae placed on milkweed (Asclepisa syriaca) and three rates of nitrogen fertiliser (0, 0.071 and 0.143g NH 4 NO 3 ) [42], found that the highest populations were on plants with the intermediate levels of fertilisation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study with Mysus persicae on grafted one-year-old peach plants and five levels of nitrogen fertilisation (0.05, 3, 6, 10 and 15 mM N from NO 3 ) [59], it was found that populations which had developed from initially placed apterous aphids, remained stable at the lowest N level, increased over time at the three intermediate levels and decreased at the highest level. Another study with populations of Aphis nerii, begun from apterae placed on milkweed (Asclepisa syriaca) and three rates of nitrogen fertiliser (0, 0.071 and 0.143g NH 4 NO 3 ) [42], found that the highest populations were on plants with the intermediate levels of fertilisation.…”
Section: Discussionmentioning
confidence: 99%
“…QualiTree, which can react to pruning, would be a good framework for future tree-aphid studies. Of course, this also calls for future consideration of nitrogen in the model because of its effect on aphid dynamics in trees (Sauge et al 2010) and more generally its implication in the trade-off between defence and growth in plant-pest interactions (Le Bot et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…These positive effects are often attributed to improvements in nitrogenous nutrition. Neutral or negative effects of nitrogen fertilization on herbivorous insect performance, however, have also been reported . Researchers have therefore proposed that there is an optimal nitrogen level in plants for herbivorous insects, and concentrations that exceed this level reduce insect fitness .…”
Section: Introductionmentioning
confidence: 99%
“…Neutral or negative effects of nitrogen fertilization on herbivorous insect performance, however, have also been reported . Researchers have therefore proposed that there is an optimal nitrogen level in plants for herbivorous insects, and concentrations that exceed this level reduce insect fitness . The optimal nitrogen concentration in plants differs among insect species or even among genotypes of the same species .…”
Section: Introductionmentioning
confidence: 99%